Kecenderungan kebebasan berfikir mahasiswa Melayu Muslim Malaysia dekad 1970-an - Muhamad Faisal Ashaari; Mohammad Hasan Sharafi Che Mohd Adli (Penerbit Universiti Kebangsaan Malaysia, 2019)
Each student era has its own distinctive thinking pattern that stimulate their activism. This can be seen in their activities in 70s. They are vocal and aggressive in mobilizing associations and groups to approach current issues in line with the young souls who have a high and passionate idealism. This is qualitative study using content analysis methodology from various sources in the form of books, journals, articles and electronic materials related to this topic. There are four factors that stimulate students’ critical thinking namely socioeconomics, dakwah, politics and the Universities and University Colleges Act (AUKU). Many of their activities are beneficial, but sometimes it is in contrary to the mainstream of society and the government policy. This article analyses the above four factors that related to 1970s Malaysian Malay student activities. Students were heavily influenced by the Nationalist Islamist idealism after the May 13, 1969 incident based on religious and national inspiration. The student movement also changed from the nationalist movement to religious-based movement that called on religion as a way of life. Malay nationalism was still a part of idea in freedom of thinking in their movement spirit following the fate of Malay community who were still retreating after independence in 1957.